Analysing the stereotypical sailor and soldier in Indian constitutional law. Issue 3 (2nd September 2021) - Gandhi, Dhruva; Ghia, Unnati
ABSTRACT: The Supreme Court of India in two landmark decisions – Secretary, Ministry of Defence v. Babita Puniya and Union of India v. Annie Nagaraja – emphatically struck down subordinate legislation governing defence forces on the basis of an anti-stereotyping principle. While these decisions have furthered Indian discrimination law by finding the use of gender stereotypes to be constitutionally impermissible, they have also left certain important questions unanswered. The interplay between Articles 15 and 33 of the Constitution remains unexplored, leaving open the possibility of the prohibition against gender discrimination being abrogated by laws pertaining to armed forces. Moreover, the scope and application of the anti-stereotyping principle are yet to be ascertained. Finally, the principle as it stands may meet with considerable difficulty if and when applied to cases outside Article 15(1), specifically those falling under Article 15(3). We argue that a different approach to the principle is warranted to accommodate such concerns.